Dynamics and Ontogenetic Condition Populations Galanthus Nivalis L. and Allium Ursinum L. in National Natural Park «Kremenet’s Mountains» - O. S. Muzychenko (Людина і довкілля: Проблеми неоекології, 2018)
Purpose. Study of the dynamics and ontogenetic condition of Galanthus nivalis L. and Allium ursinum L. in the localities of the National Natural Park «Kremenet’s Mountains». Methods. Field, statistical, analytical. Results. The present state of the localities Galanthus nivalis L. and Allium ursinum L. in the territory of the National Nature Park «Kremenet’s Mountains» was described. Affiliation of each studied populations to a certain category was determined, according to classification of T. O. Rabotnov (invasive, normal, regressive). Ontogenetic spectrum of the localities species were constructed and analyzed in the aspect of their belonging to one of the types: left-side, centered, right-side. Proportion of plants of different ontogenic states in the investigated localities was determined. On the basis of the received results there were made conclusions on the ontogenetic structure of Galanthus nivalis L. and Allium ursinum L. localities in the conditions of the National Nature Park «Kremenet’s Mountains» are made. Conclusions. In the National Nature Park «Kremenet’s Mountains» for Galanthus nivalis L. and Allium ursinum L. there are three periods and six age classes. It was established that most of populations were full nominated of normal type, and are characterized by monomodal, left-sided age spectrum with maximum on individuals of pregenerative period. In the studied localities, there were no sprouts, but the presence of juvenile specimens indicates the fullness of their age spectrum.